Cross-Dressing and Transgender Representation in Swedish Cinema, 1908–2017 - Horak, Laura (European Journal of Scandinavian Studies, 2017)
Today’s explosion of Swedish films made by and about transgender people is sometimes considered in a vacuum. This article explores the long history of cross-gender performance in Swedish cinema and the relationship of these new films to older traditions. In this article, I will outline the contours of cross-gender performance in Swedish films from the 1908 to today, using some exemplary films to display the variety of styles, genres, and meanings that can be found: the short dance film Dances Through the Ages ( Skilda tiders danser , Walfrid Bergström, 1909); the swashbuckler Lasse-Maja (Gunnar Olsson, 1941); the romantic comedy Up With Little Märta ( Fram för Lilla Märta , Hasse Ekman, 1945); the dramatic art film The Magician ( Ansiktet , Ingmar Bergman, 1958); the recent romantic comedy Cockpit (Mårten Klingberg, 2012); and the trans art film Everything Falls Apart ( Nånting måste gå sönder , Ester Martin Bergsmark, 2016). I will show that the two main shifts in Swedish cinema’s representation of cross-gender performance occurred in the mid-1950s and in the 1990s, due to social changes and changes in the structure of the Swedish film industry. In Swedish cinema, as elsewhere, cross-dressing has never meant any one thing, so we must attend to the specific contexts of its expression in order to understand what it meant.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 5-Créateur.rice LGBTQ+; _Nettoyé